2015
DOI: 10.1007/s11356-015-4427-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of multidrug-resistant halophilic bacteria from shrimp farm effluents of Parangipettai coastal waters

Abstract: Multidrug resistance of heterotrophic bacteria isolated from an aquaculture farm effluent in Parangipettai, at the southeastern coast of India, was investigated. In the initial screening, 27 antibiotic-resistant strains were isolated. All the strains were tested for antibiotic susceptibility against chloramphenicol with varying concentrations. From these, two highly resistant strains, i.e. S1 and S5, were isolated. The selected strains were identified by 16S ribosomal RNA (rRNA) sequencing techniques and confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…More important, previous work on Bacillus flexus have shown that members of this species can degrade organic [25] and inorganic [26] nitrogen, thus making it a possible candidate for bioremediation in alkaline wastewater [27]. Some strains of B. flexus also demonstrate strong phosphorus solubilization activity [28], and others demonstrated resistance to OTC [29].…”
Section: Discussionmentioning
confidence: 99%
“…More important, previous work on Bacillus flexus have shown that members of this species can degrade organic [25] and inorganic [26] nitrogen, thus making it a possible candidate for bioremediation in alkaline wastewater [27]. Some strains of B. flexus also demonstrate strong phosphorus solubilization activity [28], and others demonstrated resistance to OTC [29].…”
Section: Discussionmentioning
confidence: 99%
“…More important, previous work on Bacillus flexus have shown that members of this species can degrade organic(Guo et al 2013) and inorganic(Divyashree et al 2009) nitrogen, thus making it a possible candidate for bioremediation in alkaline wastewater(Wang and Zhao 2013). Some strains of B. flexus also demonstrate strong phosphorus solubilization activity(Gechemba et al 2015), and others demonstrated resistance to OTC(Sundaramanickam et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Los fragmentos amplificados fueron secuenciados a través del análisis de las secuencias obtenidas en cuanto a la calidad de los nucleótidos y la similitud, utilizando el programa MEGA (TAMURA et al, 2013) versión 6 con posterior comparación con las secuencias depositadas en el GenBank (BENSON et al, 2002) utilizando el Basic Local Alignment Search Tool (BLAST) ((ALTSCHUN et al, 1997).…”
Section: Estudio De La Viabilidad Bajo Diferentes Valores De Ph (Cai Et Al1999)unclassified
“…Diferentes géneros bacterianos aislados de ambiente de carcinicultura han sido identificados y evaluados con resistencia a la tetraciclina/oxitetraciclina: Bacillus (SUNDARAMANICKAM et al, 2015) y Aeromonas-Shewanella-Vibrio-Lactococcus (YANO et al, 2011) entre otros géneros.…”
Section: Bacterias Del Génerounclassified